Are pre‐service teachers disinclined to utilise embodied humanoid social robots in the classroom?. (3rd July 2021) - Istenic, Andreja; Bratko, Ivan; Rosanda, Violeta
Abstract: Teachers' readiness for technology integration depends also on their beliefs about the contribution of technology to teaching and learning, which influence their motivation for its adoption. Initial pre‐service teacher education is critical in reducing the attitude‐behaviour divide supporting technology acceptability, acceptance and use. Acceptance of interaction between human and robot is more complicated than human‐computer interaction acceptance. Social robots are radical innovations, harder for potential users to accept in human social spaces than are incremental innovations. In 2019, a survey using a convenience sample of 121 first‐year students was conducted to examine pre‐service teachers' beliefs about social robot educational technology. It examined the following factors derived from the Unified Theory of Acceptance and Use of Technology adopted for social robots in education: Perceived social dimension, Intention to use, Perceived usability, Anxiety. Based on our findings, it seems there is a critical disjunction between researchers' efforts to equip social robots with human manners and social intelligence and participants' rejection of this technology precisely because it mimics being human. Further, we report that ICT familiarity as assessed using PISA's Information Communication Technology—ICT familiarity factors is related to robot acceptability. These findings need further examination to inform educational robotics design and Human‐Robot Interaction research and teacher education and training. Practitioners notes What is already known about this topic In the age of robotic technology, teachers face requirements to prepare students for work and life with social robots. Social robots are tested for classroom integration. Teachers' readiness to implement robot lessons depends on their beliefs about social robotic technology's contribution to teaching. Research and development in the field of social robotics still tend to focus more frequently on technology applications rather than pedagogical issues and advancing teaching and learning. What this paper adds Participants refuse to accept the idea of social robot‐based instruction. The identified belief pattern is based mainly on the perceived social dimension, intention to use, perceived usability and anxiety. Participants critically perceive the robot's social dimension. Some of PISA's ICT familiarity factors are related to robots acceptability factors. Implication for policy and/or practice The policy and practice need to address how social robots could be integrated into current teaching and learning practices and more importantly how could robotic technology facilitate innovative pedagogical models for effective and efficient learning. The introduction of social robots should follow instructional design requirements and not merely technological advancement. Teacher initial education has to provide social robotic learning environments for pre‐service teachers to experiment and design.